Autoantibody-associated congenital heart block: a rare cause of persistent fetal bradycardia. (22nd May 2015) - Nigam, Aruna; Ahmad, Ayesha
Abstract : Persistent fetal bradycardia in early pregnancy is a rare finding and indicates towards congenital heart block. This is commonly associated with positive maternal anti-Ro/anti-La antibodies. A case of an asymptomatic primigravida with persistent fetal bradycardia on routine antenatal ultrasound is reported with special emphasis on its management options.